J. M. Synge’s Images of Society and Social Critique - Lachman, Michal (Hungarian Journal of English and American Studies, 2020)
J. M. Synge’s artistic contribution to the revival of the Irish theatre remains an undeniable fact. However, his consistently developed and dramatized views on the condition of Irish society, on the social and economic problems facing the newly formed state, are issues which seem to have been sidelined by critical emphasis placed on artistic and theatrical issues of his writing. This essay traces the line of Synge’s social thinking and imagery to show its continued effort to critically review the conservative, patriarchal system of values that Irish society had developed in the first decades of the twentieth century. The main part of the article concentrates on presenting the figures of dramatic protagonists who oppose the conservative social order and who simultaneously develop their independent ethical and social consciousness. The article argues that by presenting strong, Nietzschean, individuals who are vehemently rejected by their communities Synge formulates his own critical views of the Victorian and patriarchal normativity of the Irish state. (ML)